Increasing Teenagers Awareness of Early Marriage Through Drama Performances in Telaga Urung Hamlet - Ade Rizki Maulana; Islami Nurdiana; Rizwan (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
Early marriage remains a significant social issue in Indonesia, with far-reaching impacts on adolescent health, education, and well-being. This article explores the effectiveness of drama performances as a method to raise adolescent awareness of the risks of early marriage in Telaga Urung Hamlet. Through a qualitative approach with a case study design, this study involved adolescents aged 12 to 18 years who actively participated in script writing, acting training, and drama performances. The drama themes used depicted the challenges and consequences faced by those involved in early marriage. The results showed that this activity not only succeeded in attracting adolescents' interest, but also increased their understanding of the issue, followed by in-depth discussions about its impact on the community. Drama performances proved to be effective as an educational tool that educates and facilitates social dialogue, as well as encouraging positive changes in adolescent attitudes and awareness of early marriage. Thus, drama performances can be considered as an innovative strategy in efforts to address the issue of early marriage among adolescents.